Pedagogical pattern of running a course on secondary school students’ achievement in waves - Nkwo Inyang Nkwo; Margaret Ndidiamaka Anugwo; J. O. Ugama (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study investigated the comparative effectiveness of pedagogical pattern of running a course and talk-chalk methods on senior secondary school students’ achievement in waves. It is triggered by reports of persistent students’ low achievement in physics contributed largely by students’ poor performance in waves-related items. It adopted the quasi-experimental pretest-posttest control group design. Three research questions and hypotheses guided the study. There were 216 students who participated in the study. Physics Achievement Test (PAT) containing 50 multiple-choice researcher-developed items were used as instrument for data collection. Mean and standard deviation were used to answer the research questions while ANCOVA was used to test the hypotheses at 0.05 level of significance. Results showed that: the pedagogical pattern of running a course method was superior method in fostering students’ achievement in waves; female students achieved higher than male students using pedagogical pattern of running a course strategy to teach waves; and there was no significant interaction effect of teaching methods and gender on students’ achievement in waves. From the findings, it was recommended that the pedagogical pattern of running a course strategy should be used in teaching physics in secondary school education system and in training of teachers.